In-situ observations using tagged animals - Roquet, Fabien; Boehme, Lars; Bester, Marthan; Bornemann, Horst; Brasseur, Sophie; Charrassin, Jean-Benoit; Costa, Daniel; Fedak, Michael Andre; Guinet, Christophe; Hall, Ailsa Jane; Harcourt, Robert; Hindell, Mark; et al. (2017)
Marine mammals help gather information on some of the harshest environments on the planet, through the use of miniaturized ocean sensors glued on their fur. Since 2004, hundreds of diving marine animals, mainly Antarctic and Arctic seals, have been fitted with a new generation of Argos tags developed by the Sea Mammal Research Unit of the University of St Andrews in Scotland, UK. These tags investigate the at-sea ecology of these animals while simultaneously collecting valuable oceanographic data. Some of the study species travel thousands of kilometres continuously diving to great depths (up to 2100 m). The resulting data are now freely available to the global scientific community at http://www.meop.net. Despite great progress in their reliability and data accuracy, the current generation of loggers while approaching standard ARGO quality specifications have yet to match them. Yet, improvements are underway; they involve updating the technology, implementing a more systematic phase of calibration and taking benefit of the recently acquired knowledge on the dynamical response of sensors. Together these efforts are rapidly transforming animal tagging into one of the most important sources of oceanographic data in polar regions and in many coastal areas. Non peer reviewed